Pre-school education and training as factors of ethnic identity preservation of foreign Ukrainians in the USA and Canada - Rudnytska-Yuriichuk, Iryna (Cercetare şi Practică în Ştiinţele Educaţiei, Didactic and Pedagogical Publishing House, 2013)
The article discusses the peculiarities of organization and work of Ukrainian preschools in the Ukrainian diaspora in Canada and U.S., which aim to develop children’s national identity.
Keywords: children; education; national identity; preschool education; Ukrainian diaspora